Deontology or consequentialism? Ethical approach on the use and management of wildlife, illustrated by the use of caimans in Latin America - Larriera, Alejandro (Ethnobiology and Conservation, 2022)
Government decision-makers are frequently faced with the choice of enabling or maintaining conservation programs based on the sustainable use of wild species – usually beneficial to both human populations and the ecosystem - or adhering to the ethical or moral requirements of those who oppose the commercial use of animals. The purpose of this document is to discuss this conflicting situation.The continuing decline in the populations of wild species, as well as the high commercial interest in them, promoted the establishment of Sustainable Use strategies in the mid-20th century, which resulted in significant population recovery of several species. However, a growing number of Non-Governmental Organizations (NGOs) deepened the combat against the exploitation of animals for human consumption in all forms, beginning in the early 21st century and intensifying in the second decade, based on alleged ethical principles, and claiming for compassion towards wild animals. In this context, it is currently very common to observe government officials tending to ban extractive activities, more often out of fear of condemnation in social networks than based on professional conviction. In the case of management of wild species, this approach is characterized by a lack of scientific basis, empathy with indigenous and rural communities, and of concrete alternative ideas to the modes of exploitation that have been developed so far.